2016
DOI: 10.1097/bsd.0b013e31827649ea
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome of Percutaneous Endoscopic Interlaminar Lumbar Discectomy for Highly Migrated Disk Herniation

Abstract: PEID may be applied comfortably even for less-experienced surgeons because of the familiar anatomy with open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 17 publications
0
93
0
1
Order By: Relevance
“…11,15,17 Generally, a PETD is possible at all spinal levels except for L5-S1 in patients with high iliac crests. 15,18,[28][29][30] In such cases, the interlaminar route is an option, but scar tissue remains a problem as it is with open surgery. 11,15,17 Transforaminal access is not always successful in cases with a narrow neural foramen, a high iliac crest, high canal compromise, high-grade migration, and/or the presence of large vessels in the neural foramen.…”
Section: Surgical Decision and Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…11,15,17 Generally, a PETD is possible at all spinal levels except for L5-S1 in patients with high iliac crests. 15,18,[28][29][30] In such cases, the interlaminar route is an option, but scar tissue remains a problem as it is with open surgery. 11,15,17 Transforaminal access is not always successful in cases with a narrow neural foramen, a high iliac crest, high canal compromise, high-grade migration, and/or the presence of large vessels in the neural foramen.…”
Section: Surgical Decision and Techniquementioning
confidence: 99%
“…12 Dural injury was not recorded in the primary operation; if it was, we would not have chosen the PEID technique. 29 A working channel with a beveled opening (8.0 mm outer diameter) was inserted over the dilator, and an endoscope (Vertebris system; Richard Wolf, Knittlingen, Germany) was introduced after removal of the obturator. 12 After general anesthesia, intraoperative electromyographic monitoring was applied.…”
Section: Surgical Decision and Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Bernucci and Giovanelli suggested that the classic interlaminar interspace approach seems to be an acceptable surgical method for accessing a preforaminal disc herniation , and this technique was shown to be safe and did not cause any instability according to the latest follow‐up. However, the chances of root injury increase when general anesthesia is used in the interlaminar approach . Moreover, the interlaminar approach may involve severe intraoperative bleeding and a long surgical time, leading to increased postoperative pain .…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The PFEILD was described in the same year (2006), but in different locations, by Choi et al 19 and Ruetten et al, 20 and its surgical principle in the case of herniated discs, the resection of the fragments of the disc (contained, extruded, migrated or not, sequestrated, at the central or foraminal level) that are compressing the nerve structures at the L5-S1 level causing lumbar and/or radicular pain. The satisfactory outcomes of the technique, with reported improvement rates above 80%, [21][22][23][24][25][26][27] are contrasted with the significant challenge of a difficult and relatively long learning curve and the potential for complications related to the lack of technical experience, 28,29 since in PFEILD, as in most minimally invasive procedures, the clinical results are closely linked to previous training. [30][31][32] In this sense, it is important to note that the technology revolution in recent years has not only changed medicine and surgery, but also medical education, and in particular, how surgical skills are acquired.…”
Section: Introductionmentioning
confidence: 99%